SASARAN PENDIDIKAN DI TINJAU DARI KONTRUKSI AKHLAK IMAM AL GHAZALI - Subekti; Diana (An Najah (Jurnal Pendidikan Islam dan Sosial Keagamaan), 2022)
Moral education is part of the teachings of Islamic education. Even though we all know that the country of Indonesia is mostly Muslim. With good moral education, it is hoped that the values ​​of Islamic education teachings can be instilled and implemented in Indonesia. Good moral education will lead the perpetrators to become human beings with noble morals in various lines of life. Because of the importance of moral education, it needs to be reviewed and compared with the thoughts of Western figures. This article discusses how the concept of moral education in al Ghazali's perspective is compared with the thoughts of Western figures. This study is expected to contribute ideas about the concept of moral education associated with Islamic education in the present. The results of this research study show that Imam al Ghazali was a great scholar who lived in his time with a very high enthusiasm for seeking knowledge. This is all evidenced by the existence of his books which have been translated into various languages. Moral education is a conscious effort to guide and direct one's will to achieve noble behavior and make it a habit. Meanwhile, according to Western figures, morality is synonymous with morals, decency and ethics. Where less attention to the essence and consequences of the actions committed. So that it can be said that people who have good ethics even though they are against Islamic law are considered to have done good deeds.